2012
DOI: 10.3363/prb.26.101
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of Silicon-Containing Apatite Fiber Scaffolds for Bone Tissue Engineering

Abstract: The aim of this work is to develop a highly-functional tissue engineering scaffold from silicon-containing apatite fibres (Si-AF). Firstly, Si-AFs were synthesized by a homogeneous precipitation method. Starting solution with a Ca/(P+Si) ratio of 1.67 was prepared by mixing Ca(NO 3 ) 2 4H 2 O, (NH 4 ) 2 HPO 4 , Si(OC 2 H 5 ) 4 (TEOS), (NH 2 ) 2 CO and HNO 3 . The concentrations of TEOS in the starting solution were 0 (AF), 0.8 (0.8Si-AF) and 1.6 (1.6Si-AF) mass%. Next, Si-AF scaffolds (Si-AFS) were fabricated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Recently, we successfully synthesized siliconcontaining apatite fibers (Si-AFs) and fabricated a silicon-containing apatitefiber scaffold (Si-AFS) [11]. Our previous research showed that Si-AFS had a threedimensional cell culture environment and that osteoblastic cells in/on Si-AFS achieved greater proliferation better than those in/on AFS due to eluted Si ions [12,13]. This result is in good agreement with a report by Keeting et al [14].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Recently, we successfully synthesized siliconcontaining apatite fibers (Si-AFs) and fabricated a silicon-containing apatitefiber scaffold (Si-AFS) [11]. Our previous research showed that Si-AFS had a threedimensional cell culture environment and that osteoblastic cells in/on Si-AFS achieved greater proliferation better than those in/on AFS due to eluted Si ions [12,13]. This result is in good agreement with a report by Keeting et al [14].…”
Section: Introductionsupporting
confidence: 88%
“…The composition of Si-AF is described as Ca 10 (PO 4 ) 6 concentrations of TEOS were 0 (AF) and 0.8 (Si-AF) mass%, which are reported to promote bone formation and to be free from toxicity [15,16]. AF was prepared by heating the starting solution at 80°C for 24 h, followed by heating at 90°C for 72 h, while Si-AF was prepared by heating the starting solution at 80°C for 24 h, followed by heating at 95°C for 144 h [11,12]. Spherical CBs (Nikabeads; Nihon Carbon Company, Japan) with diameters measuring approximately 20 μm and 150 μm were added to the Si-AF slurry, which comprised 1 mass% Si-AFs in a mixed solvent of ethanol/water = 1/1 (v/v) at a CB/Si-AF (w/w) ratio of 1/1 or 3/ 1.…”
Section: Fabrication Of Afss and Si-afssmentioning
confidence: 99%
“…We have successfully synthesized silicon-containing apatite fibers (Si-AF) by homogeneous precipitation method [7]. Furthermore, three-dimensional silicon-containing apatite-fiber scaffold (Si-AFS) were fabricated using these Si-AFs [8]. In the present work, we will report the Si release from the Si-AFSs, together with findings of in vitro evaluation using MC3T3-E1.…”
Section: Introductionmentioning
confidence: 99%